إبرام الصفقات العمومية في ظل أحكام المرسوم الرئاسي 2 - فرج, رشيد (جامعة الوادي -University eloued, 2017)
الواضح من خلال دراستنا لموضوع الصفقات العمومية عموما، وطرق ومراحل إبرامها خصوصا، وفي ظل أحكام المرسوم الرئاسي / 247 15تحديدا، أنها تعتبر من العقود الإدارية المبرمة من طرف الدولة، ممثلة في مختلف هياكلها على المستويين المركزي والمحلي، وهي تخضع لقانون خاص ومميز، يدخل ضمن مجموعة قانونية متكاملة ، كقانون المنافسة، وقانون الممارسة التجارية، قانون مكافحة الفساد و القانون المتعلق بنفقات الدولة للتجهيز، وهي أيضا وسيلة من وسائل تجسيد فكرة إستمرار المرفق العام و ، ٕاشباع الحاجات العامة، تضمن الدولة من خلالها الحفاظ على المال العام، عن طريق منافسة تجارية نزيهة، تتم بداية بعملية إبرامها لذلك حرص المشرع الجزائري على النص على جميع الأحكام و الإجراءاتIt is clear through our study of the issue of public deals in general, and the methods and stages of their conclusion Especially, and under the provisions of Presidential Decree / 247 15 in particular, it is considered an administrative contract concluded by the state, represented in its various structures at the central and local levels, It is subject to a special and distinct law, which is part of an integrated legal group, such as the competition law. The Commercial Practice Law, the Anti-Corruption Law and the Law on State Equipment Expenditures, It is also one of the means of embodying the idea of ​​the continuation of the public utility and the satisfaction of public needs. Through it the state guarantees the preservation of public money, through fair commercial competition With the process of concluding it, the legislator was keen to الخاصة بهذه العملية، من الإشهار إلى الإسناد النهائي، وألزم الإدارة )المصلحة المتعاقدة
سياسة عامة
Keywords: إبرام الصفقات ،العمومية ، المرسوم الرئاسي 15/247; Negotiation, general Presidential Decree 15/247